Perancangan Aplikasi Penjualan Online Berbasis WEB Pada Toko Kokoon Store Lamandau - Irmayanti, Ade; Khoirunnas, Moh. Sigit (Fakultas Teknik Universitas Persada Indonesia YAI, 2024)
One of the applications needed in the business world, especially in terms of technology, is thisonline sales application. Where currently, society and businesses are influenced by technology.Moreover, when it comes to the Internet, many societies and even companies use Internetconnections for various purposes. One of them is that they can make purchases and sales online,known as e-commerce, which allows customers to make transactions anytime and anywhere. Intoday's internet era, selling shoes online has become a popular trend. However, the Kokoon StoreLamandau which sells various types of shoes does not yet have an application that can helpcustomers make purchases online. The purpose of this research is to help customers use the Internetas a tool to make purchases anytime and anywhere they want. A systematic approach modifiedinto the SDLC (System Development Life Cycle) model is used in the design and development ofthis online sales system. It is hoped that this application will help Kokoon stores increase sales andmarket their products.